An ecological analysis of prison overcrowding and suicide rates in England and Wales, 2000–2014. (January 2017) - van Ginneken, Esther F.J.C.; Sutherland, Alex; Molleman, Toon
Abstract: Prisoners are at a greatly increased risk of suicides compared to the general population. Differences in suicide risk can be partly explained by individual risk factors, but the contribution of prison characteristics remains unclear. Overcrowded prisons have higher suicide rates, but this may be related to prison function, security level, population size and turnover. The aim of the current study was to investigate the contribution of each of these prison characteristics to suicide rates, using data from the Ministry of Justice for adult prisons in England and Wales from 2000 to 2014. Negative binomial regression analysis showed that larger population size, higher turnover, higher security and public management were associated with higher suicide rates. When controlling for these factors, overcrowding was not found to be related to suicide rates. Questions remain about the causal mechanisms underlying variation in prison suicides and the impact of the lived experience of overcrowding. Further research is needed to examine the relative contribution of prison and prisoner characteristics to suicides.